Impacts Of Covid 19 Pandemic on Tourism and Hotel Employee Performance in Bandar Lampung - Atika Riasari (Al-Buhuts, 2021)
This paper aims to empirically ascertain the effect of COVID-19 pandemic on a tourism firm’s employee performance in Bandar Lampung. The purpose of this study is to obtain empirical evidence about the effect of the COVID-19 pandemic on the performance of tourism company employees in Bandar Lampung. This study achieved the objective by sourcing data via a questionnaire which was administered online to tourism company employee in Bandar Lampung. The study employed the Linear Regression to test the hypotheses stated in the study. In this study, the researcher studied the effects of the COVID-19 pandemic toward the tourism company employee performance in Bandar Lampung. Coronavirus (COVID-19) Pandemic negatively impacts the employee performance of the temporary closed down tourism businesses in Bandar Lampung.